2013
DOI: 10.1016/j.lungcan.2013.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of radiation therapy alone for elderly patients with unresected stage III non-small cell lung cancer

Abstract: Purpose Chemoradiotherapy is the standard of care for unresectable stage III non-small cell lung cancer (NSCLC). Elderly patients, who are often considered unfit for combined chemoradiotherapy, frequently receive radiation therapy (RT) alone. Using population-based data, we evaluated the effectiveness and tolerability of lone RT in unresected elderly stage III NSCLC patients. Methods and Materials Using the Surveillance, Epidemiology and End Results (SEER) registry linked to Medicare records we identified 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…1,2 Many elderly patients are unfit for chemoradiotherapy. Population studies show that high-dose radiotherapy (RT) alone is used in 11% to 41% of elderly patients with stage III NSCLC, whereas 21% to 27% receive no anticancer treatment, [3][4][5] resulting in median overall survival (OS) times of 7.6 and 6.9 months, respectively. [3][4][5] As the requirement for travel for 4-6 weeks to undergo conventional RT may discourage frail patients, 6 shorter hypofractionated RT regimens have been advocated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 Many elderly patients are unfit for chemoradiotherapy. Population studies show that high-dose radiotherapy (RT) alone is used in 11% to 41% of elderly patients with stage III NSCLC, whereas 21% to 27% receive no anticancer treatment, [3][4][5] resulting in median overall survival (OS) times of 7.6 and 6.9 months, respectively. [3][4][5] As the requirement for travel for 4-6 weeks to undergo conventional RT may discourage frail patients, 6 shorter hypofractionated RT regimens have been advocated.…”
Section: Introductionmentioning
confidence: 99%
“…Population studies show that high-dose radiotherapy (RT) alone is used in 11% to 41% of elderly patients with stage III NSCLC, whereas 21% to 27% receive no anticancer treatment, [3][4][5] resulting in median overall survival (OS) times of 7.6 and 6.9 months, respectively. [3][4][5] As the requirement for travel for 4-6 weeks to undergo conventional RT may discourage frail patients, 6 shorter hypofractionated RT regimens have been advocated. 1 Stereotactic ablative RT (SABR) is the current standard of care for unfit patients with peripheral lung cancers and has been defined by delivery of a BED 10 (biologically effective dose with a / b ¼ 10) of at least 100 Gy.…”
Section: Introductionmentioning
confidence: 99%
“…The median OS time was 9.0 months. The survival was better when using high complexity RT, but survival time was not presented separately [ 18 ]. In phase III intergroup study by Radiation Therapy Oncology Group, Eastern Cooperative Oncology Group, and Southwest Oncology Group, median OS of stage III NSCLC patients treated by lone RT was 11.4 months for standard RT arm (60 Gy) and 12 months for hyperfractionated RT arm (69 Gy) [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…But, these results were achieved mostly before modern RT technique era [ 20 ]. In a population-based study of elderly NSCLC patients, improved survival rates were only shown when high complexity RT approaches were used, and not for low complexity RT [ 18 ]. A lot of reports have shown that definitive RT dose over 60 Gy can be tolerated in older patients, as well as younger patients, and our present study result also confirms it.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, sequential administration of chemotherapy followed by radiation can avoid overlapping toxicities which might also help improve tolerability. Although radiation treatment alone likely will have little impact on long-term survival or cure and is also associated with toxicity (i.e., pneumonitis and esophagitis), it has still been shown to improve symptoms and provide some survival benefit in patients that are unfit for chemotherapy [22].…”
Section: Alternative Options For More Frail Patientsmentioning
confidence: 99%